PENENTUAN NILAI SPF EKSTRAK ETIL ASETAT DAUN MANGGA GEDONG MENGGUNAKAN SPEKTROFOTOMETRI UV - VIS - Lisnawati, Nia; N.U, M Fathan; Nurlitasari, Dwi (Jurnal Riset Kefarmasian Indonesia, 2019)
One way that is done to reduce the negative impact of sunlight is by using sunscreen. Sunscreen can protect the skin by spreading sunlight or absorbing sunlight radiation energy that is about the skin. Phenolic compounds especially flavonoid groups have the potential as a sunscreen because of the chromophore group (single conjugated double bond) capable of absorbing UV light both UV A and UV B, thus reducing the intensity of the skin. Flavonoids have three properties of photoprotektor that is UV absorption, antioxidant properties, and modulate some DNA signaling pathways. The potential of sunscreen can be expressed with Sun Protection Factor (SPF). SPF is designated as UV protection B and is not specifically intended to resist UV A and UV C. The purpose of this research is to know the value of SPF (Sun Protection Factor) of ethyl acetate extract of mango gedong leaves using UV-Vis spectrophotometry. Simplicia gedong mango leaves were extracted using ethyl acetate solvent by reflux. Gedong mango leaf extract identified flavonoid compound using 10% NaOH and H2SO4 (concentrated). Determination of SPF (Sun Protection Factor) value of med gedong leaf extract using UV-Vis spectrophotometry method. The concentration of ethyl acetate extract of mango gedong leaves used was 120 ppm, 240 ppm and 360 ppm. The SPF (Sun Protection Factor) values were analyzed using Mansur method. The result of identification of flavonoid compound showed that the extract of ethyl acetate of mango gedong leaves positively contain flavonoids, while the result of SPF (Sun Protection Factor) extract of ethyl acetate of mango gedong leaves was 5,556; 16,675 and 22,243. The SPF (Sun Protection Factor) extract of 5,556 muddy ethyl acetate leaves including moderate protection type, 16,675 and 22,243 including ultra-protection type when tested using UV-Vis spectrophotometry by Mansur method